Cascade C=O/C=C/C-N bond formation: metal-free reactions of 1,4-diynes and 1-En-4-yn-3-ones with isoquinoline and quinoline N-oxides - Zhang, Bing; Huang, Long; Hashmi, A. Stephen K. (Organic letters, 2017)
The metal-free reactions of 1,4-diynes and 1-en-4-yn-3-ones with isoquinoline and quinoline N-oxides are developed, resulting in the formation of 3,4-dihydro-2H-pyrido[2,1-a]isoquinolines and 2,3-dihydro-1H-pyrido[1,2-a]quinolines via cascade C═O/C═C/C-N bond formation. It is the first report in which in the alkyne oxidation by N-oxides both the oxygen atom of N-oxides and the nitrogen atom are involved in a second C-heteroatom bond formation. The reactions showed a broad substrate scope and functional group tolerance. Furthermore, the products were found to display green-blue fluorescence in DMSO with fluorescence quantum yields up to 0.59.